Custom Gene Capture and Next‐Generation Sequencing to Resolve DiscordantALKStatus by FISH and IHC in Lung Adenocarcinoma. Issue 11 (November 2016) - Jang, Jin Sung; Wang, Xiaoke; Vedell, Peter T.; Wen, Ji; Zhang, Jinghui; Ellison, David W.; Evans, Jared M.; Johnson, Sarah H.; Yang, Ping; Sukov, William R.; Oliveira, Andre M.; Vasmatzis, George; et al.
ABSTRACT : Introduction : We performed a genomic study in lung adenocarcinoma cases with discordant anaplastic lymphoma receptor tyrosine kinase gene ( ALK ) status by fluorescent in situ hybridization (FISH) and immunohistochemical (IHC) analysis. Methods : DNA from formalin‐fixed paraffin‐embedded tissues of 16 discordant (four FISH‐positive/IHC–negative and 12 FISH‐negative/IHC–positive) cases by Vysis ALK Break Apart FISH and ALK IHC testing (ALK1 clone) were subjected to whole gene capture and next‐generation sequencing (NGS) of nine genes, including ALK, echinoderm microtubule associated protein like 4 gene ( EML4 ), kinesin family member 5B gene ( KIF5B ), staphylococcal nuclease and tudor domain containing 1 gene ( SND1 ), BRAF, ret proto‐oncogene ( RET ), ezrin gene ( EZR ), ROS1, and telomerase reverse transcriptase ( TERT ). All discordant cases (except one FISH‐negative/IHC–positive case without sufficient tissue) were analyzed by IHC with D5F3 antibody. In one case with fresh frozen tissue, whole transcriptome sequencing was also performed. Twenty‐six concordant (16 FISH‐positive/IHC–positive and 10 FISH‐negative/IHC–negative) cases were included as controls. Results : In four ALK FISH‐positive/IHC–negative cases, no EML4‐ALK fusion gene was observed by NGS, but in one case using fresh frozen tissue, we identified EML4 –baculoviral AIP repeat containing 6 gene ( BIRC6 ) and AP2 associated kinase 1 gene ( AAK1 ) ‐ALK fusion genes. Whole transcriptome sequencing revealed a highly expressed EML4‐BIRC6 fusion transcript and a minimally expressed AAK1 transcript. Among the 12 FISH‐negative/IHC–positive cases, no evidence of ALK gene rearrangement was detected by NGS. Eleven of 12 FISH‐negative/IHC–positive cases detected by ALK1 clone were concordant by repeat ALK IHC with D5F3 antibody (i.e., FISH‐negative/IHC–negative by D5F3 clone). Among the 16 ALK FISH‐positive/IHC–positive positive controls, whole gene capture identified ALK gene fusion in 15 cases, including in one case with Huntington interacting protein 1 gene ( HIP1 ) ‐ALK . No ALK fusion gene was observed in any of the 10 FISH‐negative/IHC–negative cases. Other fusion genes involving ROS1, EZR, BRAF, and SND1 were also found. Conclusions : ALK FISH results appeared to be false‐positive in three of four FISH‐positive/IHC–negative cases, whereas no false‐negative ALK FISH case was identified among 12 ALK FISH‐negative/IHC–positive cases by ALK1 clone, which was in keeping with the concordant FISH‐negative/IHC–negative status by D5F3 clone. Our targeted whole gene capture approach using formalin‐fixed paraffin embedded samples was effective for detecting rearrangements involving ALK and other actionable oncogenes.